Genetic association of interleukin-21 polymorphisms with systemic lupus erythematosus. Issue 4 (24th August 2007) - Sawalha, A H; Kaufman, K M; Kelly, J A; Adler, A J; Aberle, T; Kilpatrick, J; Wakeland, E K; Li, Q-Z; Wandstrat, A E; Karp, D R; James, J A; Merrill, J T; et al.
Abstract : Objective: The aetiology of systemic lupus erythematosus (SLE) is incompletely understood. Both genetic and environmental factors are implicated in the pathogenesis of the disease. Herein, we describe genetic association between SLE and polymorphisms in the interleukin (IL)-21 gene. The reported effect of IL-21 on B-cell differentiation into plasma cells and its effect on dendritic cell maturation and T-cell responses make IL-21 an attractive candidate gene for SLE. Methods: Three single nucleotide polymorphisms (SNPs) in the IL-21 gene were genotyped in a total of 2636 individuals (1318 cases and 1318 controls matched for age, sex and race). Population-based case–control association analyses were performed. Results: We found a genetic association with SLE and two SNPs located within the IL-21 gene (rs907715: χ 2  = 11.55, p<0.001; rs2221903: χ 2  = 5.49, p = 0.019). Furthermore, genotypes homozygous for the risk alleles were more frequent than genotypes homozygous for the non-risk alleles in European–American patients as compared to controls (rs907715 (GG versus AA): odds ratio (OR) = 1.66, p = 0.0049; rs2221903 (GG versus AA): OR = 1.60, p = 0.025). Conclusion: Our findings indicate that IL-21 polymorphism is a candidate association with SLE. The functional effects of this association, when revealed, might improve our understanding of the disease and provide new therapeutic targets.